Long‐term follow‐up of insulin autoimmune syndrome in an elderly patient. Issue 12 (14th September 2020) - Yoshino, Hiroshi; Kawakami, Kyoko; Kohriyama, Kenji; Yoshino, Gen; Matsunaga, Shinji; Takechi, Hajime
Abstract: An 84‐year‐old man was admitted to our hospital. His blood glucose level was 20 mg/dL. Since laboratory tests showed high titers of insulin antibodies, insulin autoimmune syndrome (IAS) was diagnosed. In　order to avoid hypoglycemia, steroids can be effective in the long‐term management of IAS in elderly patients. Abstract : Prednisolone can be effectively used in long‐term management of hypoglycemia in elderly patients with Insulin Autoimmune Syndrome. Scatchard analysis for insulin autoantibodies revealed that an affinity constant and binding capacity of the autoantibodies were also improved.